Metodologia wykładu patrologi-patrystyki w Polsce po „Instrukcji” z 1989 roku - Słomka, Jan (Vox Patrum, 2008)
In 1989, the Instruction on the Study of the Fathers of the Church in the Formation ofPriests was published. A document of the Congregation for Catholic Education, it provides a basic reference point for all lecturers on patrology. In its last third part, the Instruction offers a set of specific guidelines relating to the ways patrology ought to be taught. The article aims to examine the impact of the Instruction on the textbooks that have appeared in Poland since it was published. There have been six such textbooks, including one translation, by such authors as H. Pietras (two textbooks), A. Żurek, Sz. Pieszczoch. L. Padovese and F. Drączkowski. Despite the fact that some authors quoted the Instruction in the introduction, none of them pointed towards it as a source of methodological inspiration. As for the actual method applied, the textbooks can be divided into two groups: one of them follows the classical method, represented by, e.g., the textbook by B. Altaner, limiting the presented material for practical reasons. The other group includes textbooks compiled according to entirely different methods, taking account of the guidelines presented in the Instruction. A methodological analysis of the above mentioned textbooks leads to the conclusion that there is no possibility to create a textbook that would play a universal role, similar to the work by B. Altaner and A. Stuiber. In the future, we may expect a continuation of the two trends in the method in which textbooks of patrology are written.